PENGARUH SOCIAL MEDIA MARKETING MELALUI BRAND AWARENESS DAN E-WOM TERHADAP REPURCHASE INTENTION PADA KONSUMEN KOSMETIK HALAL SARIAYU DI DKI JAKARTA - AUDREY NATHALIA; Irma Satya Indriyanti (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This purpose of this study is to find out the effect of Social Media Marketing through Brand Awareness and e-WOM on Repurchase Intention to consumers of Sariayu halal cosmetic in DKI Jakarta. This form of research uses descriptive and causal research, using a Likert scale that using 7 points in its measurement. The method of determining the sample using purposive sampling method with primary and secondary data. The sample used as many as 208 female respondents who met the criteria. This research used SEM (Structural Equation Modeling) with SmartPLS 3.2.9 as a test tool. The results obtained in this study that Brand Awareness and e-WOM have an influence on Repurchase Intention to consumers of Sariayu halal cosmetic in DKI Jakarta, but Social Media Marketing has no effect on Repurchase Intention.